Developing countries' economic fundamentals and FDI inflows: The moderating role of institutions - Gildas Kadoukpè Magbondé; Mamadou Abdoulaye Konté (Cogent Economics & Finance, 2022)
This paper provides evidence on the moderating effects of institutions on the marginal effects of human capital, financial development, and macroeconomic policies on foreign direct investment (FDI) inflows, based on large panel data of 124 developing countries-spanning from 2002 to 2018-and generalised method of moments (GMM) estimators. The findings suggest that only financial development has a positive and significant direct effect on FDI inflows to developing countries. Importantly, improving the quality of institutions moderates the marginal effect of human capital on FDI inflows. Drawing on these findings, policymakers in developing countries are advised to undertake a set of reforms to upgrade the quality of institutions, improve financial institutions and markets, and scale up investments in human capital.
Keywords: 330; Human capital; financial development; macroeconomic policies; institutions; FDI; GMM estimators; developing countries